1995
DOI: 10.1111/j.1365-2044.1995.tb05949.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new method for determining tracheal tube length in children

Abstract: SummaryMost paediatric tracheal tubes are marked in centimetres from the tip. In 105 children, nasotracheal tube length was set at the level of the vocal cords such that all 3.0 and 3.5mm internal diameter tubes were placed with the 3 cm mark at the cords, all 4.0 and 4.5 tubes were set at 4 cm at the cords and all 5.0 and 5.5 tubes were set at 5 cm at the cords. Subsequent chest X ray showed that 79% of the tracheal tubes were in the ideal midtracheal position, one tube was marginally short and 20% of the tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 9 publications
3
30
0
Order By: Relevance
“…Freeman et al (4) reported that the midtracheal positioning of the ETT could be achieved in 79% of patients aged 0 -14 yr by setting the tube length at the level of the vocal cord, such that an ETT with an internal diameter of 3.0 and 3.5 could be set 3 cm from the tip at the cords, 4.0 and 4.5 tubes at 4 cm, and 5.0 and 5.5 tubes at 5 cm. The advantage of this technique is that it is easily remembered and setting the tube length at the level of the vocal cord reduces the variability due to the length of the upper airway.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Freeman et al (4) reported that the midtracheal positioning of the ETT could be achieved in 79% of patients aged 0 -14 yr by setting the tube length at the level of the vocal cord, such that an ETT with an internal diameter of 3.0 and 3.5 could be set 3 cm from the tip at the cords, 4.0 and 4.5 tubes at 4 cm, and 5.0 and 5.5 tubes at 5 cm. The advantage of this technique is that it is easily remembered and setting the tube length at the level of the vocal cord reduces the variability due to the length of the upper airway.…”
Section: Discussionmentioning
confidence: 98%
“…The ETT can be displaced as a result of the neck movement causing accidental endobronchial intubation or extubation from the trachea (1,4). Therefore, it is extremely important to accurately place the ETT to a predetermined depth to ensure safety during neck movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the cuff would lie in the subglottic space, between the vocal cords, or even in the supraglottic space if the tubes are placed either according to radiological criteria or to an age-related formula for predicting depth of tube insertion [1,9,10]. Excessive subglottic pressure can cause mucosal ischemia, fibrosis, and lead to stenosis by compression of the mucosa against the nonexpandable cricoid cartilage [1].…”
Section: Discussionmentioning
confidence: 99%
“…As the assistant removes the orotracheal tube, the nasotracheal tube is gently advanced through the vocal cords; the Magill forceps should not be used to advance the tracheal tube through the vocal cords, as this may cause trauma to the glottis. Several methods of estimating the depth of insertion of nasotracheal tubes have been described [189][190][191], although the following formula [190] works well for children up to 4 years of age:…”
Section: Nasal Tracheal Intubationmentioning
confidence: 99%